2008
DOI: 10.1080/13880200802179634
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Spanish Medicinal Plants for Antioxidant and Antifungal Activities

Abstract: Dichloromethane, ethyl acetate, methanol, and aqueous extracts obtained from 16 Spanish medicinal plants were screened for their antioxidant and antifungal activities. The radical scavenging capacity was evaluated by the DPPH method using a rapid screening by TLC and a spectrophotometric assay. Polar extracts obtained from Jasonia gluti-, and Lythrum salicaria L. (Lythraceae) showed high antioxidant properties. Among them, the methanol extract of Lythrum salicaria showed the strongest antiradical capacity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 45 publications
1
29
1
3
Order By: Relevance
“…Four different methods were used for the evaluation of the antioxidant activity of the extracts: DPPH radical-scavenging assay (Lopez et al, 2008), 2,2'-azinobis-(3-ethylbenzthiazoline-6-sulphonic acid (ABTS + ) assay (Almajano, Carbo, Jimenez, & Gordon, 2008), Oxygen Radical Absorbance Capacity (ORAC) assay (Almajano, Delgado, & Gordon, 2007) and Ferric Reducing Antioxidant Power (FRAP) method (Skowyra, Falguera, Gallego, Peiró, & Almajano, 2013). Results were expressed as mg Trolox (TE)/g of freeze-dried weight (FDW) extract.…”
Section: Quantitative Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Four different methods were used for the evaluation of the antioxidant activity of the extracts: DPPH radical-scavenging assay (Lopez et al, 2008), 2,2'-azinobis-(3-ethylbenzthiazoline-6-sulphonic acid (ABTS + ) assay (Almajano, Carbo, Jimenez, & Gordon, 2008), Oxygen Radical Absorbance Capacity (ORAC) assay (Almajano, Delgado, & Gordon, 2007) and Ferric Reducing Antioxidant Power (FRAP) method (Skowyra, Falguera, Gallego, Peiró, & Almajano, 2013). Results were expressed as mg Trolox (TE)/g of freeze-dried weight (FDW) extract.…”
Section: Quantitative Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Additionally, biologically active compounds have been isolated from the plant such as oleanolic acid and ursolic acid as antifungal compounds and the hexahydroxydiphenoyl ester vescalagin as an antibacterial agent (Becker et al, 2005). Antioxidant activity of various extracts of the plant has been tested, and polar extracts were found to be the most active ones (Coban et al, 2003;Lopez et al, 2008;Tunalier et al, 2007). The plant extract decreases the blood glucose level in both hyperglycaemic and normoglycemic rats and rabbits (Lamela et al, 1986;Torres and Suarez, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the cytotoxic assay confi rmed that growth and proliferation of the cancer cell lines are predominantly infl uenced by triterpene derivatives and sterols of this plant. ., 2003;Lopez et al, 2008;Tunalier et al, 2007). The plant extract decreases the blood glucose level in both hyperglycaemic and normoglycemic rats and rabbits (Lamela et al, 1986;Torres and Suarez, 1980).…”
mentioning
confidence: 99%
“…Moreover, four sesquiterpenes isolated from Jasonia glutinosa D.C. (Asteraceae), namely lucinone, glutinone, 5-epikutdtriol and kutdtriol, have been evaluated for their in vitro anti-inflammatory activity in cellular systems generating cyclooxygenase (COX) and 5-lipoxygenase (5-LOX) metabolites (Benito et al, 2002). López et al (2008) have been demonstrated the antioxidant and antifungal activities of this plants. Therefore, the antioxidant activity of these herb used in the present study may contribute to the reduction of the oxidative activity of AlCl 3 induced AD.…”
Section: Expression Of App Bace1 Bace2 and Cox-2 Genesmentioning
confidence: 99%
“…According to López et al (2008), plant material was air-dried in the dark at room temperature. The dried-powder (180 meshes) was successively extracted 3-times with 200 ml dichloromethane, ethyl acetate, methanol, and water after maceration at 4°C for 24h.…”
Section: Preparation Of Medicinal Plant Extractsmentioning
confidence: 99%